Peningkatan Perilaku Prososial Siswa di Sekolah melalui Layanan Bimbingan Kelompok dengan Teknik Modeling - Hastha Purna Putra; Nurhizrah Gistituati; Syahniar Syahniar (Jurnal Konseling dan Pendidikan, 2015)
The low prosocial behavior of students can inhibit the developmental tasks of adolescent such as the inability of appreciating others and getting others’ respect. Group guidance can be used to improve students’ prosocial behavior. The aim of this study was to reveal the effectiveness of group guidance service with modeling techniques in improving students’ prosocial behavior. This quasi-experimental research with pretest and posttest control group design aims to find out whether group guidance services with modeling techniques can improve students' prosocial behavior or not. Two groups were selected by using purposive sampling. They were selected from Sekolah Menengah Pertama Islam Terpadu (SMPIT) Rabbi Radhiyya Curup Tengah and Madrasah Tsanawiyah Pesantren Muhammadiyah Curup Timur. Each group consisted of 10 students. There were five meetings of group guidance service for each experimental and control group. The data of prosocial behavior were collected by using pretest and posttest, then they were analyzed by using the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Sample with SPSS version 16.00. The findings of this study were: (1) there was a significant difference between students’ pretest and posttest of prosocial behavior in the experimental group, (2) there was a significant difference between students’ pretest and posttest of prosocial behavior in the control group, (3) there was a significant difference between posttests of students’ prosocial behavior in the experimental and the control group. Based on those findings, it is concluded that the students’ prosocial behavior can be improved through group guidance with modeling techniques. Therefore, it is suggested for counseling teachers to do group guidance by using modeling techniques, especially in enhancing prosocial behavior and other social behaviors.